Rola islamistycznej przemocy politycznej na Zachodzie w tworzeniu mechanizmów autocenzury - Wójcik, Jan (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The subject of this article is an analysis of the terrorist attacks perpetrated by the members of the jihadist movement against artists, journalists, activists, and politicians who have violated Islamic sacrum. In addition, the author discusses their influence on initiating self-censorship mechanisms with regard to issues considered seditious by Muslims. Furthermore, the author attempts to diagnose the contemporary state of Western societies in the context of protecting freedom of speech and artistic expression and in opposition to sharia law, which is contrary to those ideas. The presented article reveals the extent to which non-government alagents (in this instance – the jihadist organizations) effectively limit the openness of public debate
Keywords: przemoc polityczna; terroryzm; islamizm; karykatury Mahometa; islam; wolność słowa; bluźnierstwo; cenzura; autocenzura